Crushed bricks as aggregate in cement based binder. Issue 1 (January 2021) - Palovcik, J; Opravil, T; Soukal, F; Masilko, J
Abstract: The work deals with the impact of crushed brick on properties of Portland cement binder. The source of brick recycled materials is not only the demolition waste, but also the waste from brick production. One way to reduce the amount of this recyclate is to use it in cement-based composite. The advantages of using bricks as aggregate are their lower bulk density compared to conventional aggregates. Economic and ecological benefits are also important, because less natural sources need to be mined. First, the phase composition of used brick aggregate, its particle size and morphology were analysed. Test specimens with different content of brick recyclate were prepared and tested for the mechanical properties. Subsequently, the microstructure of prepared samples was examined using a scanning electron microscope. The phase composition of samples was analysed by X-ray diffraction analysis.